MODEL KONSELING KECAKAPAN HIDUP UNTUK MENGEMBANGKAN KESEJAHTERAAN PSIKOLOGIS MAHASISWA DI KABUPATEN BONE - Syahril, - (2022)
ABSTRACT Syahril. (2021). Life Skills Counseling Model to Develop Psychological Well-Being of Students in Bone Regency. Supervised by Prof. Dr. Cece Rakhmat, M.Pd. (promoter), Prof. Dr. Syamsu Yusuf LN, M.Pd. (co-promoter), Dr. Ilfiandra, M.Pd. (member). Guidance and Counseling Study Program, Faculty of Education, Universitas Pendidikan Indonesia. This research is motivated by the existence of students who have low student psychological well-being. The purpose of this study is to produce a model of life skills counseling to develop students' psychological well-being. The research procedure was carried out in three stages, namely the preliminary stage, model development and model testing. The research design used was mixed methods research with Explanatory Sequential Mixed Methods Design. The respondents of this research were 225 students from the Tarbiyah faculty of IAIN Bone, which aimed to determine the tendency of students' psychological well-being. Field test as many as 12 students. The instrument used is a psychological well-being scale adapted from Ryff which measures the dimensions of independence, environmental management, personal growth, positive relationships with others, life goals and self-acceptance. Test the effectiveness of the life skills counseling model to improve psychological well-being using Wilcoxon analysis. The results showed (1) the tendency of students' psychological well-being in general was in the high category, (2) Life skills counseling model in developing students' psychological well-being was carried out through the stages of needs analysis, modeling, validation of counseling and psychology experts, and model testing. (3) The results of the Wilcoxon statistical test show that the life skills counseling model is effective in improving the psychological well-being of students, both overall and in terms of psychological well-being. The results of the study are recommended for further research and counselors at universities and the Chancellor of IAIN Bone Keywords: life skills counseling, psychological well-being, thinking and acting skills ABSTRAK Syahril. (2021). Model Konseling Kecakapan Hidup untuk Mengembangkan Kesejahteraan Psikologis Mahasiswa di Kabupaten Bone. Dibimbing oleh Prof. Dr. Cece Rakhmat, M.Pd. (promotor), Prof. Dr. Syamsu Yusuf LN, M.Pd. (ko-promotor), Dr.Ilfiandra, M.Pd. (anggota). Program Studi Bimbingan dan Konseling Fakultas Ilmu Pendidikan Universitas Pendidikan Indonesia. Penelitian ini dilatarbelakangi oleh adanya mahasiswa yang memiliki kesejahteraan psikologis mahasiswa yang rendah. Tujuan penelitian ini adalah menghasilkan model konseling kecakapan hidup untuk mengembangkan kesejahteraan psikologis mahasiswa. Proseder penelitian ini dilakukan dalam tiga tahap yaitu tahap pendahuluan, pengembangan model dan uji coba model Disain penelitian yang digunakan adalah mixed methods research dengan Explanatory Sequential Mixed Methods Design. Responden peneltian ini Mahasiswa fakultas Tarbiyah IAIN Bone berjumlah 225 mahasiswa yang bertujuan untuk mengetahui kecenderungan kesejahteraan psikologis mahasiswa. Uji lapangan sebanyak 12 mahasiswa. Instrument yang digunakan adalah skala kesejahteraan psikologis yang diadaptasi dari Ryff yang mengukur dimensi kemandirian, pengelolaan lingkungan, pertumbuhan pibadi, relasi postif dengan orang lain, tujuan hidup dan penerimaan diri. Uji efektivitas model konseling kecakapan hidup untuk meningkatkan kesejahteraan psikologis menggunakan analisis Wilcoxon. hasil penelitian menunjukkan (1) kecenderungan kesejahteraan psikologis mahasiswa secara umum berada pada kategori tinggi, (2) Model konseling kecakapan hidup dalam mengembangkan kesejahteraan psikologis mahasiswa dilakukan melalui tahap analisis kebutuhan, penyusunan model, validasi ahli BK dan Psikologi, dan uji coba model. (3) Hasil uji statistik Wilcoxon menunjukkan model konseling kecakapan hidup efektif meningkatkan kesejahteraan psikologis mahasiswa baik secara keseluruhan maupun perdimensi kesejahteraan psikologis. Hasil penelitian direkomendasikan untuk penelitian selanjutnya dan konselor di perguruan tinggi dan Rektor IAIN Bone Kata kunci: konseling kecakapan hidup, kesejahteraan psikologis, kecakapan berpikir dan bertindak